A Study Case of Dilemmatic Situations Decision Making Tendency: Ethics or Morality? From the Perspective of Indonesian EFL Teachers - W. D, Hermayanti,; Eri, Kurniawan; Antarini, Antarini; K, Suryatama (Journal of Education Research, 2024)
People make decisions throughout their day and most of decision making do not require much thought, however, when situations are more complicated, it is easy to feel hesitant. This hesitation creates two terms in decision making; moral and ethical. In teachers’ situation, their obligations and personal beliefs can, and sometimes do, conflict while deciding something. Hence, this study aims to seek for the tendency whether EFL teachers in Indonesia use ethical or moral guidance in making decision in dilemmatic situations and also to reveal their reasons in making those decisions. This study also investigates the relation between age and service time or experience as a teacher affecting their tendency in making decision. Mixed methods in the form of open-ended questionnaires with clustered-random sampling for selecting the 30 participants are used in this study. The findings show that ethical decision is the most used type of decision with duty-based ethical decision as the prominent reasoning. It was also found that, while insignificant, female participants made more ethical decisions than man. It was also revealed that the longer the experience one possesses, the more ethical decision will be made